1994
DOI: 10.1159/000276633
|View full text |Cite
|
Sign up to set email alerts
|

Decongestion Effect and Rebound Swelling of the Nasal Mucosa during 4-Week Use of Oxymetazoline

Abstract: The aim of this study was to investigate whether long-term use of oxymetazoline induces a rebound swelling of the nasal mucosa and whether the decongestion effect is altered during medication. Eight healthy volunteers had oxymetazoline nasal spray (0.5 mg/ml; 0.1 ml in each nostril, three times daily) for 30 days and registrations of the mucosal surface positions were made using rhinostereometry. Compared to the registrations before the start of medication, no rebound swelling was registered after 10 days. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
45
1
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 6 publications
4
45
1
1
Order By: Relevance
“…After 1 month of medication, rebound swelling and an increase in histamine sensitivity was recorded which reflected rhinitis medicamentosa and nasal hyperreactivity [12,13]. The results, therefore, con firmed the clinical observation that rhinitis medicamen tosa is indistinguishable from vasomotor rhinitis [14][15][16],…”
supporting
confidence: 60%
See 2 more Smart Citations
“…After 1 month of medication, rebound swelling and an increase in histamine sensitivity was recorded which reflected rhinitis medicamentosa and nasal hyperreactivity [12,13]. The results, therefore, con firmed the clinical observation that rhinitis medicamen tosa is indistinguishable from vasomotor rhinitis [14][15][16],…”
supporting
confidence: 60%
“…We have shown that the mucosal swelling after hista mine provocation was the same for the oxymetazoline and xylometazoline groups in all four histamine provoca tion tests [12,13], The rebound swelling after 30 days on both drugs were also the same. Therefore, for the purpose of this study, the results from the oxy-and xylometazoline groups were analyzed together.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In fact, the symptom scores show that the nasal stuffiness starts already after 3-day use of the nasal decongestant spray. With rhinostereometry we have previously shown that oxymetazoline nasal spray induces mucosal congestion and nasal hyperreactivity, as indicated by increased hista mine sensitivity, in healthy subjects after 30 days but not after 10 days [11], The increase in histamine sensitivity was in agreement with that seen in patients with vasomo tor rhinitis and it was greater than that of healthy subjects [12,13]. In another study, we investigated two groups of healthy subjects who received oxymetazoline nasal spray with and without benzalkonium chloride for 10 days [14].…”
Section: Discussionmentioning
confidence: 99%
“…Эти явления ухудшают вентиляцию назальной и параназальной полостей и дополнительно вызывают изменения способности к мукоцилиарному клиренсу, что может привести к застою секрета или длительному сохра-нению медиаторов воспаления в слизистой оболочке носа, но главным образом к неспособности выведения вирус-ных, бактериальных и грибковых патогенов. Лекарствен-ный ринит связан с использованием лекарственных средств, содержащих, в частности, эфедрин, тогда как для современных сосудосуживающих средств этот эффект менее характерен и встречается реже [8,9].…”
unclassified